1970
DOI: 10.1111/j.1945-5100.1970.tb00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Analyses of the Murchison and Lost City Meteorites

Abstract: The abundances of 22 elements have been determined in the recently fallen Murchison and Lost City meteorites. Analyses were performed by 14‐MeV neutron activation, thermal neutron activation, and in a few cases by wet chemical techniques. On the basis of these data the composition of the Murchison chondrite is intermediate between previously reported analyses of Type II and Type III carbonaceous chondrites. The data for the Lost City chondrite in general agree well with mean values reported for H‐group ordinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1971
1971
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 8 publications
(5 reference statements)
1
8
0
Order By: Relevance
“…However, the soluble iron is a small percentage of the total iron in the material. In the Murchison meteorite, a range of iron contents between 204 to 237 mg/g is reported in five studies (Ehmann et al 1970;Jarosewich 1971;Fuchs et al 1973;Genge and Grady 1999;Wolf and Palme 2001) with a mean of 218.8 mg/g. Four studies report ranges of 194 to 234 mg/g in the Cold Bokkeveld meteorite (von Michaelis et al 1969;Wilk 1969;Genge and Grady 1999;Wolf and Palme 2001) with a mean of 209.6 mg/g.…”
Section: Microbial Weathering Of Meteoritesmentioning
confidence: 99%
“…However, the soluble iron is a small percentage of the total iron in the material. In the Murchison meteorite, a range of iron contents between 204 to 237 mg/g is reported in five studies (Ehmann et al 1970;Jarosewich 1971;Fuchs et al 1973;Genge and Grady 1999;Wolf and Palme 2001) with a mean of 218.8 mg/g. Four studies report ranges of 194 to 234 mg/g in the Cold Bokkeveld meteorite (von Michaelis et al 1969;Wilk 1969;Genge and Grady 1999;Wolf and Palme 2001) with a mean of 209.6 mg/g.…”
Section: Microbial Weathering Of Meteoritesmentioning
confidence: 99%
“…Initial chemical classification of the meteorite was carried out by Ehmann et al (1970), Jarosewich (1971) and Lovering et al (1971). Fuchs et al (1973) In the 1960s, radioastronomy indicated the presence of carbon-rich molecules in space.…”
Section: Compositionmentioning
confidence: 99%
“…Approximately 100 kg of this carbonaceous chondrite was recovered. Ehmann et al (1970) have analyzed the Murchison meteorite for 22 elements and found that the composition is intermediate between a type II and type III carbonaceous chondrite. The bulk chemical analysis of this meteorite has also been reported by Jarosewich (1971).…”
Section: Introductionmentioning
confidence: 99%
“…These values are uncertain due to faulty positioning of the Nd standard during irradiation. c. Ehmann et al (1970) specimen: NMNH #4848.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation